Psychological distress: a study with portuguese nursing students - Varela, Ana (2013)
This research highlights the importance of psychological distress in academic life. Research on this topic helps us to achieve greater knowledge and adds relevant implications for well-being in higher education. Future directions for research and practise are also discussed.